« Aujourd’hui, nous avons enfin une patrie ! » L’appartenance nationale chez les jeunes hommes d’un quartier populaire de la Caracas post-Chávez - Henry Moncrieff Zabaleta (Cahiers des Amériques Latines)
This article raises the problem of belonging "to the homeland" in Venezuela, a nation subsumed in a long standing political and economic crisis. Based on a visual ethnography guided by a photo-elicitation with young males, I analyze how they experience their nationalist roots after Chávez´s death. I focus especially on a popular neighborhood located in the hills of Caracas, a mountainous geography that concentrates the harshest conditions of socioeconomic exclusion in the Venezuelan capital. These areas have been historically affected by structural deprivation and violence. This analysis seeks to understand the forms of social identification of the children of the Bolivarian Revolution, a generation that was born during the implementation of the socialist project in Venezuela, over the last 20 years. The young people I met, between 2014 and 2017, must manage their own subjectivity in the face of the partisan polarization and the transformations of the country, thus seeking to build roots and attachment in an environment marked by food shortages, police abuse, urban violence and forced migration. In this sense, the fact that they "feel part of" Venezuela can be interpreted as a symbolic interpellation of the Bolivarian state, a performative policy figuring predispositions, practices and borders among young people, as well as violence, loyalties, cruelties and indolences that point out broken belongings and radical identifications.